Microfluidic-Based Miniaturization as well as Genomics- and Metabolomics-Guided Prioritization of Bacterial Producer Strains Leverages the Numbers Game to Discover and Characterize Bioactive Natural Products - Brinkmann, Stephan; Justus Liebig University Giessen (My University, 2022)
Over the past few decades, about two-thirds of the small molecule drugs in application are based on microbial natural products (NPs) and their analogs. The undisputed success notwithstanding, the continuous increase of antimicrobial resistance and a high rate of rediscovery of NPs applying traditional cultivation and screening methods pose a serious threat to modern medicine and agriculture. Modern high-throughput microfluidic-based approaches as well as omics-based technologies are proven complementary and beneficial alternatives in order to discover novel NP scaffolds and combat this crisis. In this study, droplet-based microfluidic approaches have been developed and implemented for high-throughput microbial cultivation and screening. First, more than a thousand axenic cultures were retrieved from a soil sample and their antimicrobial activities were evaluated. The cultured strains were affiliated to five phyla (57 genera) including one member of the Acidobacteria phylum (genus Edaphobacter). Based on this droplet-based microfluidic approach and with the aim of setting up a more complex, multi compartment, and high-throughput microfluidic assay, a technical method to encase the previously generated agarose-solidified droplets with a further agarose shell has been successfully developed and validated. In parallel, the traditional activity-based discovery of NPs has been supplemented with genomics and metabolomics technologies to study the entire phylum of the Bacteroidetes – a taxonomic branch that has not been intensively explored in relation to the production of NPs. Computational prediction tools (i.e., antiSMASH, BiG-SCAPE) were used to determine the biosynthetic gene cluster (BGC) amount, type, distribution, as well as diversity to rate the biosynthetic potential encoded within the genomes of 600 Bacteroidetes strains. It revealed a genetic repertoire comparable towards classical NP producer taxa of a few genera, rather than a general ability of the entire phylum-members. A metabolomics analysis of the outstanding genus Chitinophaga (25 strains) confirmed the genomic-based prediction by revealing a chemical space not able to be assigned to any microbial NP identified today, except of the antimalarial compound Falcitidin. Based on this datasets, several bioactive natural products have been isolated, characterized and their structures have been elucidated by performing extensive UHPLC-MS/MS and NMR experiments supplemented by Marfey’s analysis. While the novel cyclic lipodepsipeptides chitinopeptins A–D exhibit broad antimicrobial activity, the lipoamino acids are active against Moraxella catarrhalis FH6810, and the identified pentacitidins (linear pentapeptides with a C-terminal aldehyde) act as parasitic cysteine protease inhibitors with an additional low-micromolar inhibition of α-chymotrypsin. Putative non-ribosomal peptide synthetase BGCs corresponding to the structural features of the chitinopeptins and the pentacitidins have been discovered and similar BGCs have been found in further Chitinophaga genomes. This work contributes to the field of NP research as it states the enormous potential of microfluidic-based high-throughput cultivation and screening assays by establishing and advancing complex agarose-solidified droplet-based microfluidic approaches. Furthermore, omics and isolation studies performed as part of this work highlight the phylum Bacteroidetes as an exciting bioresource capable of producing novel NP scaffolds, many of which await discovery.
Keywords: Natural Products; Microfluidics; Genomics; Metabolomics; Bacteroidetes; ddc:570